Autoestima e autoimagem de mulheres idosas. Sob o olhar de produtoras de conteúdos digitais em uma rede social - Custódio, Júlia (2022)
Introduction: With the increase in life expectancy, the age distribution of the world population has changed to older ages. Along with these changes, the epidemiological transition and the increase in the feminization of old age were also born. Recent studies have shown that low self-esteem and the difficulty of accepting self-image among women aged 60 years or older, together with the constant search to meet stereotypes of society, have become common and capable of generating several biopsychosocial losses, including depression. Therefore, it is essential that professionals from different areas go beyond the limits of the clinical model of care, aiming to meet the needs of each person in their entirety, focusing on innovative actions. General objective: to understand and analyze behaviors, manifestations and positions of older women, content producers, on relational aspects of self-esteem and self-image in profiles of a social network (Instagram). Method: The current project is a pluviometric study, of a qualitative, descriptive, and documentary nature of netnographic, exploratory and transversal character, with an interdisciplinary theoretical focus in the field of Sciences, Technologies and Society and Gerontology, being determined by analysis, for a short period of time. Related to qualitative aspects, their central objective is the observation of content production and interactions, provided by networks, between older women and their followers in social networks (FONSECA, 2002).